Changes in functional connectivity in newly diagnosed self‐limited epilepsy with centrotemporal spikes and cognitive impairment: An MEG study. Issue 12 (21st November 2022) - Li, Yihan; Chen, Jinan; Sun, Jintao; Jiang, Ping; Xiang, Jing; Chen, Qiqi; Hu, Zheng; Wang, Xiaoshan
Abstract: Purpose: Our purpose was to explore the relationship between cognitive impairment and neural network changes in patients newly diagnosed with self‐limited epilepsy with centrotemporal spikes (SeLECTS). Methods: The Wechsler Intelligence Scale for Children, fourth edition was used to divide all SeLECTS patients into two groups: patients with full‐scale intelligence quotient (FSIQ) below 80 that corresponded to cognitive impairment, and patients with FSIQ above 80 that corresponded to a normal cognitive function. The data on the resting state were recorded using magnetoencephalography. The properties of the networks were analyzed using graph theory (GT) analysis. Results: The functional connectivity (FC) of the frontal cortex in patients with FSIQ < 80 was reduced in the 12–30 Hz frequency band, and the FC of the posterior cingulate cortex was reduced in the 80–250 and 250–500 Hz frequency bands. The GT analysis showed that patients in the FSIQ < 80 group had higher strength in the 8–12 and 12–30 Hz frequency bands than those in the healthy control and FSIQ > 80 group. However, the path length was reduced in the 80–250 Hz band, and the clustering coefficient was reduced in the 12–30, 80–250, and 250–500 Hz frequency bands. Moreover, the receiver operator characteristic analysis showed that the clustering coefficient in the 12–30 and 80–250 Hz frequency bands, as well as the path length in the 80–250 Hz frequency band possessed a good discriminative ability in distinguishing the FSIQ > 80 group. Conclusions: SeLECTS patients with cognitive impairment in the early stage of the disease developed disordered networks in cognitive‐related brain regions. The clustering coefficient in the 12–30 and 80–250 Hz frequency bands as well as the path length in the 80–250 Hz frequency band might be good indicators to distinguish the cognitive impairment of SeLECTS patients at the early stage. Abstract :